HABITAÇÃO E SANEAMENTO BÁSICO E SUAS IMPLICAÇÕES SOCIOAMBIENTAIS - Vione, Cristiane Ivete Bugs; Kischner, Patrícia; Fernandes, Sandra Beatriz Vicenci; Uhde, Leonir Terezinha (Salão do Conhecimento, 2019)
Diagnóstico sobre saneamento e habitação